News frames of Gulf Crisis in the Arab TV Channels - Fadel, Ali Abbas; Abdalhassan, Mustafa A. (Al-Adab Journal, 2021)
The research aims to know the news frames that were promoted or neglected by the "Al-Jazeera and Al-Arabiya" channels in dealing with the events related to the Gulf crisis. This research is considered a descriptive research, as it used the survey method using the content analysis method for a regular random sample of the main news bulletins in the two channels, through a content analysis form prepared for this purpose and subject to arbitration by a group of experts in the field of media and political science to determine the validity of its paragraphs.The researcher reached a number of results, the most important of which is that it showed the main frames for the Gulf crisis in terms of content for the two channels in eight main frames, which are (the frames proposed for resolving the crisis, conflict frames, crisis causes frames, economic frames, strategic frames, legal frames, humanitarian frames, and impact frames). The consequences of the crisis) with the variation in the size of selection and promoted or neglected between the two channels, as Al-Jazeera came first in promoted the categories of frames: (the frames proposed to resolve the crisis, conflict frames, strategic frames, legal frames) while Al Arabiya channel promoted the frames: (Economic frames for the causes of the crisis, frames for the implications of the crisis) The visibility of each channel to certain frames and its superiority over the other is consistent with the policies of each country that the channel follows.